Can the prehospital National Early Warning Score identify patients most at risk from subsequent deterioration?. Issue 8 (13th May 2017) - Shaw, Joanna; Fothergill, Rachael T; Clark, Sophie; Moore, Fionna
Abstract : Introduction: The National Early Warning Score (NEWS) aids the early recognition of those at risk of becoming critically ill. NEWS has been recommended for use by ambulance services, but very little work has been undertaken to date to determine its suitability. This paper examines whether a prehospital NEWS derived from ambulance service clinical observations is associated with the hospital ED disposition. Methods: Prehospital NEWS was retrospectively calculated from the ambulance service clinical records of 287 patients who were treated by the ambulance service and transported to hospital. In this cohort study, derived NEWS scores were compared with ED disposition data and patients were categorised into the following groups depending on their outcome: discharged from ED, admitted to a ward, admitted to intensive therapy unit (ITU) or died. Results: Prehospital NEWS-based ambulance service clinical observations were significantly associated with discharge disposition groups (p<0.001), with scores escalating in line with increasing severity of outcome. Patients who died or were admitted to ITU had higher scores than those admitted to a ward or discharged from ED (mean NEWS 7.2 and 7.5 vs 2.6 and 1.7, respectively), and in turn those who were admitted to a ward had higher pre-hospital NEWS than those who were discharged (2.6 vs 1.7). Conclusion: Our findings suggest that the NEWS could successfully be used by ambulance services to identify patients most at risk from subsequent deterioration. The implementation of this early warning system has the potential to support ambulance clinician decision making, providing an additional tool to identify and appropriately escalate care for acutely unwell patients.